Association of Anesthetic Exposure Time With Clinical Outcomes After Endovascular Therapy for Acute Ischemic Stroke - Raming, Lorenz; Moustafa, Haidar; Prakapenia, Alexandra; Barlinn, Jessica; Gerber, Johannes; Theilen, Hermann; Siepmann, Timo; Pallesen, Lars-Peder; Haedrich, Kevin; Winzer, Simon; Reichmann, Heinz; Linn, Jennifer; et al. (Frontiers in Neurology, 2019)
Background: The optimal sedative regimen with general anesthesia (GA) or conscious sedation for patients undergoing endovascular therapy (EVT) remains controversial. Apart from sedative regimen, the duration of anesthetic exposure may affect clinical outcomes. We aimed to determine whether there is an association between anesthetic exposure time and clinical outcomes in mechanically ventilated stroke patients undergoing EVT for large vessel occlusion. Methods: This was an observational study of consecutive ischemic stroke patients who underwent EVT for anterior circulation large vessel occlusion under GA from January 2016 to March 2018. To minimize confounding by indication, we restricted our analysis to patients whose anesthetic exposure lasted less than 72 hours. Multivariable logistic regression modeling adjusted for covariates was employed to evaluate whether 90-days independent functional outcome (defined as modified Rankin Scale scores 0-2) and 90-days survival could be predicted by anesthetic exposure time. Results: During the study period, 138 patients with ischemic stroke who underwent EVT received GA and fulfilled our study criteria: median age was 77 years (interquartile range, 65-82); 46.4% were men; median NIHSS score was 18 (15-21), median ASPECT score was 7 (6-8). Median duration of GA was 5.4 (2.5-19.7) hours. Logistic regression modeling revealed an independent association between duration of anesthetic exposure and both 90-days independent functional outcome (p=0.034) and 90-days survival (p=0.011). Each additional 15-minutes of anesthetic exposure decreased the likelihood of achieving an independent functional outcome at 90 days by 1.5% and of being alive at 90 days by 1.0%. Conclusion: Our data promotes the notion that ischemic stroke patients who require peri-interventional GA for EVT should be extubated as soon as possible after the procedure.